Effects of international trade on education: evidence from China shock in Brazil - Souza Júnior, Evânio Marques de (2024)
In this work, we explore the exposure to trade with China to identify the causal effect of international trade on enrollment in Brazilian municipalities. We employ an instrumental variable approach, where the source of trade exposure among regions of the country varies depending on economic specialization. We find evidence that regions more exposed to exports to China are associated with a reduction in the proportion of people enrolled in basic education. Several pieces of evidence indicate that the variation in enrollment may be induced by an increase in the opportunity cost of education due to increased in income for individuals of school age.